Effect of Theobroma cacao Polyphenol on Isoproterenol-Induced Myocardial Infarction in Wistar Rats - Chioma Assumpta Anosike, Iwunze Chisom Cajetan (Journal of Applied Pharmaceutical Science, 2015)
The effect of Theobroma cacao (cocoa) polyphenol on isoproterenol-induced myocardial infarction in Wistar rats was studied. Polyphenol was extracted from cocoa using hydroalcohol solvent. Twenty four rats divided into six groups of four rats each were used for the study. Groups 3, 4, 5 and 6 were pretreated with the extract (300, 500 and 700 mg/kg) and 100 mg/kg of atenolol respectively before administration with isoproterenol. Group 1 served as normal control and group 2 was administered with isoproterenol without treatment. The activities of marker enzymes, aspartate amino transferase (AST), alanine amino transferase (ALT) and lactate dehydrogenase (LDH) in both serum and heart tissue homogenate were assayed. Cocoa polyphenol ameliorated the leakage of marker enzymes from the heart into the serum and also restored the levels of these enzymes in the cardiomyocytes. Histological examination of heart tissues revealed marked ability of the extract to reduce the progression of infarct lesions.
Keywords: Isoproterenol, polyphenol, myocardial infarction, cocoa, rats.